Hacking wireless networks for dummies - Beaver, Kevin; Davis, Peter (Wiley Pub. Inc., 2005)
Provides information on wireless hacking, covering such topics as wardriving, denial-of-service attacks, encryption, and authenticating users.
Includes bibliographical references (p. 327-340) and index
Keywords: Wireless LANs -- Amateurs' manuals; Drahtloses lokales Netz; Eindringerkennung